Investigation of Staphylococcus strains with heterogeneous resistance to glycopeptides in a Turkish university hospital - Cagatay Atahan A; Derbentli Sengul; Nakipoglu Yasar; Katranci Handan (BMC Infectious Diseases, 2005)
Abstract Background The hetero-glycopeptide intermediate staphylococci is considered to be the precursor of glycopeptide intermediate staphylococci especially vancomycin intermediate Staphylococcus aureus (VISA). For this purpose, we aimed to investigate the heterogeneous resistance to glycopeptide and their frequencies in 135 Staphylococcus strains. Methods Heterogeneous resistance of Staphylococcus strains was detected by inoculating the strains onto Brain Heart Infusion agar supplemented with 4 mg/L of vancomycin (BHA-V4). Agar dilution method was used for determining MICs of glycopeptides and population analysis profile was performed for detecting frequency of heterogeneous resistance for the parents of selected strains on BHA-4. Results Eight (6%) out of 135 Staphylococcus strains were exhibited heterogeneous resistance to at least one glycopeptide. One (1.2%) out of 81 S. aureus was found intermediate resistance to teicoplanin (MIC 16 mg/L). Other seven strains were Staphylococcus haemolyticus (13%) out of 54 coagulase negative staphylococci (CoNS). Six of the seven strains were detected heterogeneously reducing susceptibility to vancomycin (MICs ranged between 5–8 mg/L) and teicoplanin (MICs ranged between 32–64 mg/L), and one S. haemolyticus was found heterogeneous resistance to teicoplanin (MIC 32 mg/L). Frequencies of heterogeneous resistance were measured being one in 106 – 107 cfu/ml. MICs of vancomycin and teicoplanin for hetero-staphylococci were determined as 2–6 folds and 3–16 folds higher than their parents, respectively. These strains were isolated from six patients (7%) and two (4%) of health care wokers hands. Hetero-VISA strain was not detected. Conclusion Heterogeneous resistance to glycopeptide in CoNS strains was observed to be significantly more emergent than those of S. aureus strains (vancomycin P 0.001, teicoplanin, P 0.007). The increase MICs of glycopeptide resistance for subpopulations of staphylococci comparing with their parents could be an important clue for recognizing the early steps in the appearance of VISA strains. We suggested to screen clinical S. aureus and CoNS strains, systematically, for the presence of heterogeneously resistance to glycopeptide.